2008
DOI: 10.1016/s1808-8694(15)31385-9
|View full text |Cite
|
Sign up to set email alerts
|

Efferent auditory system: its effect on auditory processing

Abstract: The study group had lower OAE suppression values and higher acoustic reflex sensitization values when compared to the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
6

Year Published

2011
2011
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
1
24
0
6
Order By: Relevance
“…12 Our results are also similar with those of another study showing that the mean suppression values in controls were higher than those in the study group, which suggested a decreased inhibitory effect in the auditory efferent system of subjects with disordered auditory processing. 9 There was no agreement with regards to the presence of contralateral acoustic reflexes and DPOAE suppression in both ears in the entire sample (Tables 5 and 6). Thus, we suggest that the efferent function assessed by DPOAE suppression testing is related with improved speech understanding in noisy environments, as ambient noise has a similar intensity to that of the test.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…12 Our results are also similar with those of another study showing that the mean suppression values in controls were higher than those in the study group, which suggested a decreased inhibitory effect in the auditory efferent system of subjects with disordered auditory processing. 9 There was no agreement with regards to the presence of contralateral acoustic reflexes and DPOAE suppression in both ears in the entire sample (Tables 5 and 6). Thus, we suggest that the efferent function assessed by DPOAE suppression testing is related with improved speech understanding in noisy environments, as ambient noise has a similar intensity to that of the test.…”
Section: Discussionmentioning
confidence: 90%
“…9 The result is that speech understanding in competing noise is compromised, as auditory efferent fibers are activated in the presence of loud noise, altering the mechanics of outer hair cells, thereby reducing the quality of the sound message. 10 The contraction of intratympanic muscles and the ability to discriminate sounds in the presence of noise are regulated by the superior olivary complex; 11 thus, it is possible that altered acoustic reflexes may compromise speech intelligibility in noisy environments.…”
Section: Discussionmentioning
confidence: 99%
“…There was no statistically significant difference in the Study group (Table 1) or in the Control group (Table 2). After having these results, the data from the two ears were combined, according to Burguetti & Carvallo 13 . We investigated if the TEOAE amplitudes without and with noise varied between the two groups ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Middle-and long-latency auditory evoked potentials, as well as suppression of otoacoustic emissions (OAEs), have shown promise as early diagnostic parameters when considered in conjunction with auditory processing activities [Burguetti and Carvallo, 2008;Durante and Carvallo, 2008;Schochat et al, 2010]. Generated by normal nonlinear mechanisms within the cochlea, OAEs are thought to be the result of motile activity by the outer hair cells, which are innervated by the efferent nerve fibers of the olivocochlear bundle [Dallos, 1992;Rasmussen, 1946].…”
Section: Introductionmentioning
confidence: 99%